Dampak Budaya Kerja dalam Meningkatan Kinerja Pegawai di Dinas Pariwisata, Pemuda dan Olahraga Kabupaten Pesisir Selatan - Mutia Aprila Erman; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This study is describes the impact of work culture in improving employee performance in DISPARPORA South Coastal Regency.The method used in this research is descriptive qualitative, in the form of written or spoken words from people and observable behavior, it is said that because this method describes or explains the problems that exist by providing answers to the problems presented. Informant selection is done by a purposive sampling method. according to the research that has been done can be said that the impact of work culture improving the performance of employees in DISPARPORA South Coastal District has not had a good impact because there are still some problems that researchers encounter related to work culture, among others: lack of awareness of employees’ time to come and go home on time,employees often delay time in completing workers to impact the achievement of unstable performance, communication between employees has not been good so that the lack of cooperation in carrying out duties, and the lack of appreciation and strict sanction given to employees.